McDowell, 1801 - Ferraguto, Federico (Revista Eletrônica Estudos Hegelianos, 2018)
In this paper, I will make some observations on McDowell’s interpretation of the development of classical German philosophy and put forth some of the theoretical questions that form the background of his interpretation of Hegel’s philosophy. I will focus on the chapter on self-consciousness in the Phenomenology of the Spirit in a wider historical context. This wider historical context involves not only a re-elaboration of the Kantian philosophy present in the Phenomenology of the Spirit itself, but also the other texts and authors who, in a certain way, motivated its development. Finally, I will try to show, through a reinstatement of McDowell’s interpretation of Hegel’s Differenzschrift (1801), that every ontology presupposes a non-subjective transcendentalism which can be found in the rational realism of Reinhold and Bardili, as well as in Fichte’s later philosophy.